Stylo: Um Framework Voltado para o Desenvolvimento de Aplicações Baseadas em Vídeo Digital - Silva, Julio César Ferreira da (2011)
The progress of science and technology coupled with the improvement of communication networks favoring the emergence of services to handle with growing volumes of data and the high transmission power available. Applications based on digital video are increasingly popular. They are widespread in multiples fields: telemedicine, artistic performances, techno-scientific events, entertainment, and advertising, among others. Proportionately, they are increasingly required higher levels of quality and delivery times getting shorter for the development of software systems. Therefore, this paper aims to map the state of the art in the development of applications based on digital video and show the necessity of having a framework that provides an abstraction for the development of systems in this area. Finally, is presented a case study of STYLO, a software framework that aims to encapsulate experiences in developing technologies that scope, providing ways for developers to reuse, usability and standardization of code and bringing greater productivity in their implementations.